APLIKASI PENDIDIKAN HOLISTIK DALAM KONTEKS INTEGRATED LEARNING - Achmad Ruslan Afendi (STKIP Paris Barantai, 2010)
Education of holistik is prestigious approach for forming of chlid character. A lot of the role of family in forming of chlid character. Family as foundation and bases which must be supported by education institute and public. Cultural and structural approach to be implemented with seriousness, plan and aim. Education strategy of family character with byword, inuring and teaching in istiqomah. Condition of morale friction and behavior can be overcome of course hardly depended from our awareness together to strive it. Education of holistik is synergistic education between Iessons in school with reality in public.